Kajian Penambahan Konsentrasi CMC Terhadap Mutu Jelly Drink Pala (Myristica fragrans Houtt) - Rumalean, Amirudin; Tetelepta, Gilian; Palijama, Syane (Universitas Pattimura, 2024)
This aims of this research was to determine the best nutmeg jelly drink with the addition of CMC concentration based on chemical and organoleptic properties. This research was designed using a single factor Completely Randomized Design with five levels of treatment with the addition of CMC concentration, namely 1.5 %, 2 %, 2.5 %, and 3 %. The research results with the addition of 1.5 % CMC concentration were the best treatment in making nutmeg jelly drink with chemical characteristics, namely pH of 4.0, total acid of 0.98 %, and total dissolved solids of 27 °Brix. Based on the hedonic properties, it is liked by panelists in term of taste, texture, suction power, and overall, and produces a jelly drink that tastes nutmeg, chewy, and easy to suck.